Effect of Moderate Intensity Activities and Soymilk Consumption on Decreasing Metabolic Syndrome Parameters - Waluya, Nandang A; Sakti, Bani; Rohyadi, Yoseph; Suhanda, Parta (Gaceta Médica de Caracas, 2023)
Introduction: The prevalence of metabolic syndrome (MetS) in Indonesia tends to increase. This MetS has an impact on increasing morbidity and mortality rates due to Non-Communicable Diseases (NCDs) such as coronary heart disease (CHD), stroke, and diabetes mellitus (DM). Monitoring and controlling MetS is an important effort to be made in preventing the increase of NCDs. Simple and easy efforts include maintaining moderate activity in daily living and consuming soymilk while maintaining a healthy lifestyle. The purpose of the study was to analyze the effect of daily moderate-intensity activity and soymilk consumption on MetS parameters.